[Book Review] Hope Circuits: Rewiring Universities and Other Organizations for Human Flourishing by Jessica Riddell - Abrahamson, Earle (Teaching and Learning Inquiry, 2024)
Book review of Hope Circuits: Rewiring Universities and Other Organizations for Human Flourishing by Jessica Riddell.